An infant with X‐linked anhidrotic ectodermal dysplasia with immunodeficiency presenting with Pneumocystis pneumonia: A case report. Issue 11 (16th November 2021) - Toyohara, Miwako; Kajiho, Yuko; Toyofuku, Etsushi; Takahashi, Chie; Owada, Keiho; Kanda, Shoichiro; Harita, Yutaka; Ohnishi, Hidenori; Wada, Taizo; Imai, Kohsuke; Kanegane, Hirokazu; Morio, Tomohiro; et al.
Abstract: Pneumocystis jirovecii pneumonia associated with primary immunodeficiency should be considered in infants with slowly progressing cyanosis, even without fever or respiratory symptoms. Genetic counseling is crucial for incontinentia pigmenti families in advance of pregnancy because lethal infections can occur before the diagnosis of X‐linked anhidrotic ectodermal dysplasia with immunodeficiency. Abstract : Pneumocystis jirovecii pneumonia in primary immunodeficiency (ID) should be considered in slowly progressing cyanotic infants. Prenatal genetic counseling is crucial to prevent fatal infection in X‐linked anhidrotic ectodermal dysplasia with ID.